Ecological status assessment of fishery water bodies in relation to ecosystem service provision - Karaim, O. A.; Biedunkova, O. O.; Tsos, O. O.; Lavrynyuk, Z. V. (Man and Environment. Issues of Neoecology, 2026)
Purpose. To assess the ecological status of fishery water bodies in the context of ecosystem service provision based on the analysis of key hydrochemical indicators and determination of their influence on the functioning of aquatic ecosystems. Methods. Analytical, computational, and comparative methods, hydrochemical analysis, and ecological classification methods for assessing water quality in fishery water bodies. Results. The ecological status of a fishery technological water body was assessed in the context of ecosystem service provision based on the analysis of key hydrochemical indicators. It was found that most of the studied parameters correspond to water quality classes II–III, indicating an overall good to satisfactory condition of the aquatic environment. Supporting ecosystem services are realized at high and satisfactory levels due to the stability of the acid–base regime and adequate oxygen conditions. Regulating services related to self-purification processes and nutrient cycling are predominantly provided at a satisfactory level, reflecting a moderate level of organic loading. Provisioning ecosystem services are also characterized by a satisfactory level, indicating the preservation of water suitability for fishery use. At the same time, certain deviations were identified, particularly elevated concentrations of total iron, which may affect the functioning of the aquatic ecosystem. The generalization of results based on block indices revealed a transitional character of water quality between good and satisfactory conditions. Conclusions. Assessing the ecological status of fishery water bodies through the lens of ecosystem services enables the integration of water quality characteristics with the analysis of ecosystem functioning. The ecological status directly determines the effectiveness of supporting, regulating, and provisioning ecosystem services, while certain hydrochemical indicators may act as limiting factors for their full realization. The proposed approach provides an opportunity for a more comprehensive assessment of fishery water bodies and can be used to improve monitoring systems and water resource management based on the ecosystem approach and principles of sustainable development.